Identifikasi Spesies Nematoda Meloidogyne sp pada Tanaman Tomat (Solanum lycopersicum L) dan Seledri (Apium graveolens L) di Samarinda - Igensius Balkan (Mulawarman University, 2019)
Nematodes are harmful organisms for tomato and celery plants. The aim of this research is to know Meloidogynespecies that attack tomato and celery plants. The locations are in Lempake and in Sambutan, Samarinda city, EastKalimantan. Identification of nematode species is based on morphometric and perennial parten characteristics. Nematodeextract was performed by root stenning method and nematode surgery. The result showed that there was one species(Meloidogyne javanica) of nematode at root of tomato and celery plant in Lempake, while in Sambutan showed that therewere two species of Meloidogyne, they are Meloidogyne javanica and Meloidogyne incognita. Based on this research showedthat nematodes Meloidogyne are the most enermoust nematodes on tomato and celery plants in Samarinda.